Sea Cucumber Derived Triterpenoid Glycoside Frondoside A: A Potential Anti-Bladder Cancer Drug - Ruizhen Ru; Gengzhan Chen; Xiaoxia Liang; Xudong Cao; Lihong Yuan; Minjie Meng (Nutrients, 2023)
Bladder cancer is a highly recurrent disease and a common cause of cancer-related deaths worldwide. Despite recent developments in diagnosis and therapy, the clinical outcome of bladder cancer remains poor; therefore, novel anti-bladder cancer drugs are urgently needed. Natural bioactive substances extracted from marine organisms such as sea cucumbers, scallops, and sea urchins are believed to have anti-cancer activity with high effectiveness and less toxicity. Frondoside A is a triterpenoid glycoside isolated from sea cucumber, Cucumaria frondosa. It has been demonstrated that Frondoside A exhibits anti-proliferative, anti-invasive, anti-angiogenic, anti-cancer, and potent immunomodulatory effects. In addition, CpG oligodeoxynucleotide (CpG-ODN) has also been shown to have potent anti-cancer effects in various tumors models, such as liver cancer, breast cancer, and bladder cancer. However, very few studies have investigated the effectiveness of Frondoside A against bladder cancer alone or in combination with CpG-ODN. In this study, we first investigated the individual effects of both Frondoside A and CpG-ODN and subsequently studied their combined effects on human bladder cancer cell viability, migration, apoptosis, and cell cycle in vitro, and on tumor growth in nude mice using human bladder cancer cell line UM-UC-3. To interrogate possible synergistic effects, combinations of different concentrations of the two drugs were used. Our data showed that Frondoside A decreased the viability of bladder cancer cells UM-UC-3 in a concentration-dependent manner, and its inhibitory effect on cell viability (2.5 μM) was superior to EPI (10 μM). We also showed that Frondoside A inhibited UM-UC-3 cell migration, affected the distribution of cell cycle and induced cell apoptosis in concentration-dependent manners, which effectively increased the sub-G1 (apoptotic) cell fraction. In addition, we also demonstrated that immunomodulator CpG-ODN could synergistically potentiate the inhibitory effects of Frondoside A on the ...